2007
DOI: 10.1677/erc-06-0073
|View full text |Cite
|
Sign up to set email alerts
|

IGF axis gene expression patterns are prognostic of survival in epithelial ovarian cancer

Abstract: The IGF axis has documented growth-promoting effects in various malignancies, but its role in epithelial ovarian cancer (EOC) has not been adequately examined. We studied the expression of the IGF axis genes in relation to outcome in EOC. Microarray expression profiles from 64 patients with advanced-stage EOC were used. Two multi-gene subsets were chosen, one upstream of the IGF receptor ('IGF family') and the other downstream of the IGF receptor ('IGF signaling pathway'), and analyzed in relation to survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 42 publications
0
36
0
1
Order By: Relevance
“…Preclinical findings implicated IGF1 in the induction of cell proliferation and invasion (Cao et al 2007, Lau & Leung 2012. Furthermore, the positive effect of IGF1 on ovarian cancer progression was supported by the correlation of increased IGF1 expression in cancer tissues with disease progression (Brokaw et al 2007) or poor prognosis (Spentzos et al 2007). Similarly, IGF2 gene expression was found to be increased in tumors with poor prognosis (Sayer et al 2005, Lu et al 2006 and to be an independent predictor of poor survival (Sayer et al 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Preclinical findings implicated IGF1 in the induction of cell proliferation and invasion (Cao et al 2007, Lau & Leung 2012. Furthermore, the positive effect of IGF1 on ovarian cancer progression was supported by the correlation of increased IGF1 expression in cancer tissues with disease progression (Brokaw et al 2007) or poor prognosis (Spentzos et al 2007). Similarly, IGF2 gene expression was found to be increased in tumors with poor prognosis (Sayer et al 2005, Lu et al 2006 and to be an independent predictor of poor survival (Sayer et al 2005).…”
Section: Discussionmentioning
confidence: 90%
“…This finding is also supported by our result in human ovarian cancer tissue, as per which a strong positive correlation between the expression of P-cadherin and phospho-IGF-1R was identified and was more predominant in the corresponding metastasis. The interaction between P-cadherin and IGF-1R is also especially interesting in view of the fact that IGF-1R is frequently overexpressed in ovarian cancer and confers a poor clinical prognosis (Spentzos et al, 2007). Similar associations between IGF-1R expression and adverse prognosis are also described in other cancer models, including breast, lung and colon cancer (Dunn et al, 1998;Takahari et al, 2009;Yim et al, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…In this context, we have found that P-cadherin was able to transactivate the insulin-like growth factor-1 receptor in regulation of p120 ctn signaling (our unpublished observations). This is also relevant to the clinical situation as insulin-like growth factor-1 receptor is frequently overexpressed in ovarian cancer and confers adverse prognosis (Spentzos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%